Experimental Study on Heat Transfer Coefficient and Friction Factor of Al2O3 Nanofluid in a Packed Bed Column - Rao, G. Srinivasa; K. V., Sharma; Chary, S. P.; R. A., Bakar; M. M., Rahman; K., Kadirgama; M. M., Noor (Faculty Mechanical Engineering, UMP, 2011)
The forced convection heat transfer coefficient and friction factor are determined for the flow of water and nanofluid in a vertical packed bed column. The analysis is undertaken in the laminar and transition Reynolds number range. The column is filled with spherical glass beads as the bed material. The heat transfer coefficients with Al2O3 nanofluid increased by 12% to 15% with the increase of volume concentration from 0.02% to 0.5% compared with water. The experimental values of axial temperature are in good agreement with the NTU-ε method proposed by Schumann’s model.